Kinetics study of photocatalytic activity of flame-made unloaded and Fe-loaded CeO2 nanoparticles - D. Channei (2018)
Unloaded CeO 2 and nominal 0.50, 1.00, 1.50, 2.00, 5.00, and 10.00 mol% Fe-loaded CeO 2 nanoparticles were synthesized by flame spray pyrolysis (FSP). The samples were characterized to obtain structure-activity relation by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), Brunauer, Emmett, and Teller (BET) nitrogen adsorption, X-ray photoelectron spectroscopy (XPS), and UV-visible diffuse reflectance spectrophotometry (UV-vis DRS). XRD results indicated that phase structures of Fe-loaded CeO 2 nanoparticles were the mixture of CeO 2 and Fe 2 O 3 phases at high iron loading concentrations. HRTEM images showed the significant change in morphology from cubic to almost-spherical shape observed at high iron loading concentration. Increased specific surface area with increasing iron content was also observed. The results from UV-visible reflectance spectra clearly showed the shift of absorption edge towards longer visible region upon loading CeO 2 with iron. Photocatalytic studies showed that Fe-loaded CeO 2 sample exhibited higher activity than unloaded CeO 2 , with optimal 2.00 mol% of iron loading concentration being the most active catalyst. Results from XPS analysis suggested that iron in the Fe 3+ state might be an active species responsible for enhanced photocatalytic activities observed in this study. © 2013 D. Channei et al.